(untitled) (Research, Society and Development, 2021)
Objective: to apprehend the social representations of nursing students about empathy in the care of burned patients. Method: qualitative research carried out through a semi-structured interview with 12 undergraduate nursing students from a public state university in Paraná, who underwent mandatory academic practices at a Burns Treatment Center. The data were treated by content analysis and discussed in the light of the Theory of Social Representations. Results: four empirical categories emerged: 1) Conceptual representations of empathy; 2) Representations of empathy as a pillar of the subjectivity of care; 3) Representations of empathy as support for the nurse’s professional practice and; 4) Personal representations about the empathy experienced by academics. Empathy was configured as an auxiliary tool in the consolidation of comprehensive care and aroused other social skills in the participants, ensuring humanized care. Conclusion: Empathy has a positive impact on the care of burned patients, and it is necessary to encourage it since the academic training so that professionals acquire a look focused on the perspective of their clientele, allowing the strengthening of care, bonding, communication and ethics.